2011
DOI: 10.1309/ajcp1llx8qmdxhho
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of p16 and ProExC Immunostaining in the Detection of High-Grade Cervical Intraepithelial Neoplasia and Cervical Carcinoma

Abstract: We compared the efficacy of p16 and ProExC immunostaining in detecting cervical intraepithelial neoplasia (CIN) 2+ in 136 formalin-fixed, paraffin-embedded cervical tissue specimens with consensus diagnoses of normal cervix, CIN 1, CIN 2, CIN 3, and carcinoma. Diffuse staining patterns of more than half the thickness of CINs and more than 10% of carcinoma cells were scored as positive. The positivity of p16 and ProExC increased significantly with the severity of cervical lesion (P < .001). For CIN 2+ or CIN 3+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 25 publications
2
29
1
1
Order By: Relevance
“…There is evidence to suggest that a negative feedback mechanism controlling p16 levels in normal cells is disrupted by a reduction of pRb activity in proliferating squamous epithelial cells expressing HR-HPV E7 (16). With regard to p16, it has been demonstrated that almost 100% of cases of HSIL and SCC associated with HR-HPV express high levels of p16, whereas non-dysplastic cervical epithelium or low-grade SIL (LSIL) associated with low-risk (LR) or negative HPV types do not express p16 (17). Ki-67 is a nuclear protein and is detected by mindbomb E3 ubiquitin protein ligase-1 (MIB-1), a monoclonal antibody that is associated with RNA transcription and cell cycle progression (18).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence to suggest that a negative feedback mechanism controlling p16 levels in normal cells is disrupted by a reduction of pRb activity in proliferating squamous epithelial cells expressing HR-HPV E7 (16). With regard to p16, it has been demonstrated that almost 100% of cases of HSIL and SCC associated with HR-HPV express high levels of p16, whereas non-dysplastic cervical epithelium or low-grade SIL (LSIL) associated with low-risk (LR) or negative HPV types do not express p16 (17). Ki-67 is a nuclear protein and is detected by mindbomb E3 ubiquitin protein ligase-1 (MIB-1), a monoclonal antibody that is associated with RNA transcription and cell cycle progression (18).…”
Section: Introductionmentioning
confidence: 99%
“…ProEx C positive expression seems to be more specifically associated with SIL than Ki-67 positive expression (Conesa-Zamora et al, 2009). ProExC immunostaining, when compared with p16 immunostaining, have similar specificity for CIN 2+ and higher specificity for CIN 3+ but lower sensitivity for CIN 2+ and CIN 3+ (Guo et al, 2011). Some reports suggested that ProExC can be more selective and informative for the progression of low-grade (CIN1) and moderate-grade (CIN2) lesions than Ki67 (Beccati et al, 2008).…”
Section: Proliferation Markersmentioning
confidence: 87%
“…p16 and vimentin (32,33). Previous studies found that p16INK4a had failed in distinguishing ECa and its expression was also related to a carcinogenesis mechanism involving HPV infection.…”
Section: Discussionmentioning
confidence: 99%